The Impact of Feedback in Response to Self-Disclosure on Social Connection: a Possible Analog Component Model of the Therapy Relationship - (:unkn) unknown (My University, 2014)
The efficacy of psychotherapy interventions has been demonstrated on a wide range of disorders. However, little is known about the specific mechanisms that influence symptom improvements. The therapeutic relationship, a well-established common factor of treatment, has been suggested to provide significant impact on treatment outcome and may be a potential mechanism of change in psychotherapy. The current study evaluates a theoretical micro-mechanism model of the therapeutic relationship; specifically, the process of providing feedback to self-disclosure statements with the intention of increasing feelings of connectedness. Ninety-eight undergraduate students were randomized to either 1 of 2 brief connection-generating dyadic interaction groups receiving minimal feedback or natural feedback to self-disclosure statements or to a control group. Those individuals who received natural feedback to self-disclosure responses had significantly greater increases in feelings of connectedness compared to those in the other conditions. Our results present preliminary support for the proposed micro-mechanism, further investigation is merited.
Keywords: Connectedness; Interpersonal; Mechanisms; Self-Disclosure; Therapeutic Relationship; Treatment Outcome